The New Inflation : The politics of prices and incomes - Jones, Aubrey (Harmondsworth ; Baltimore : Penguin, 1973)
This book gave an insights into an explanatory phenomenon about inflation as seen in contemporary political and economic terms.
Includes bibliographical references and index.
osc 26/05/17
Loans
Keywords: Wage-price policy; Inflation (Finance); Great Britain